Varying Hypopnea Definitions Affect Obstructive Sleep Apnea Severity Classification and Association With Cardiovascular Disease - Won, Christine H.J. (J Clin Sleep Med, 2018)
STUDY OBJECTIVES: To compare clinical features and cardiovascular risks in patients with obstructive sleep apnea (OSA) based on ≥ 3% desaturation or arousal, and ≥ 4% desaturation hypopnea criteria. METHODS: This is a cross-sectional analysis of 1,400 veterans who underwent polysomnography for suspected sleep-disordered breathing. Hypopneas were scored using ≥ 4% desaturation criteria per the American Academy of Sleep Medicine (AASM) 2007 guidelines, then re-scored using ≥ 3% desaturation or arousal criteria per AASM 2012 guidelines. The effect on OSA disease categorization by these two different definitions were compared and correlated with symptoms and cardiovascular associations using unadjusted and adjusted logistic regression. RESULTS: The application of the ≥ 3% desaturation or arousal definition of hypopnea captured an additional 175 OSA diagnoses (12.5%). This newly diagnosed OSA group (OSA(new)) was symptomatic with daytime sleepiness similarly to those in whom OSA had been diagnosed based on ≥ 4% desaturation criteria (OSA(4%)). The OSA(new) group was more obese and more likely to be male than those without OSA based on either criterion (No-OSA). However, the OSA(new) group was younger, less obese, more likely female, and had a lesser smoking history compared to the OSA(4%) group. Those with any severity of OSA(4%) had an increased adjusted odds ratio for arrhythmias (odds ratio = 1.95 [95% confidence interval 1.37–2.78], P = .0155). The more inclusive hypopnea definition (ie, ≥ 3% desaturation or arousal) resulted in recategorization of OSA diagnosis and severity, and attenuated the increased odds ratio for arrhythmias observed in mild and moderate OSA(4%). However, severe OSA based on ≥ 3% desaturation or arousals (OSA3%/Ar) remained a significant risk factor for arrhythmias. OSA based on any definition was not associated with ischemic heart disease or heart failure. CONCLUSIONS: The most current AASM criteria for hypopnea identify a unique group of patients who are sleepy, but who are not at increased risk for cardiovascular disease. Though the different hypopnea definitions result in recategorization of OSA severity, severe disease whether defined by ≥ 3% desaturation/arousals or ≥ 4% desaturation remains predictive of cardiac arrhythmias. COMMENTARY: A commentary on this article appears in this issue on page 1971. CITATION: Won CH, Qin L, Selim B, Yaggi HK. Varying hypopnea definitions affect obstructive sleep apnea severity classification and association with cardiovascular disease. J Clin Sleep Med. 2018;14(12):1987–1994.